Directional cues affect the collective behaviour of self-propelled particles in one dimension - Mishra P.K.; Puitandy A.; Mishra S. (My University, 2025)
This study explores the effect of quenched disorder on the characteristics of self-propelled particles in one dimension. Here, particles interact with disorder which serve as directional cues. The study investigates how the density of the directional cues influences the emergence of ordering and clustering in the collection of the self-propelled particles. We introduce the microscopic model as well as corresponding coarse-grained equations of motion for the local density and the orientation of particles. Directional cues affect the macroscopic ordering in the system, the size of the ordered clusters decays algebraically with density of cues. Further, in the presence of directional cues, a big macroscopic cluster breaks into small clusters, leading to the localization of particles around it and resulting in high density around the cues. Copyright © 2024 EPLA.